Regional growth theory - Richardson, Harry W. (London : Macmillan, 1973)
This book examines the nature of the regional growth process.
includes index.
Includes bibliographical references: p. 237-253
oo 22/01/2019
Loans
Keywords: Regional economics; Economic development; Space in economics